PENERAPAN TEKNIK PEMODELAN DALAM MENULIS TEKS FAIT DIVERS - Imam Aji Safari, - (2018)
This paper are made to examine the application of modeling technique in writing fait divers texts. The implementation is aimed to the learners who study french, specially in the competence of writing for write the text fait divers and using a text model for help learners. The steps of the modeling technique, is: 1) the learners read a text model; 2) the teachers are asking some questions to the learners for knowing their comprehension the learners; 3) after asking some questions for the first time, the teacher will demande the learners for telling their individual experiences; 4) the learners write the text like the text example; 5) the learners revise the texts and use the example text for support them; 6) the learners edited the text for knowing the use of ortograph in text; 7) the teacher give the note based of the evaluation of the competence of writing skills CECRL DELF A2.---- Ce mini mémoire se fait pour savoir l'application de la technique modélisation dans la production du texte fait divers. La mise en œuvre s'adresse aux apprenants qui apprennent le français, surtout la compétence d'écrire un texte fait divers en utilisant un texte modéle pour aider les apprenants. Les étapes de la technique modélisation sont: 1) les apprenants lisent le texte modéle; 2) l'enseignant pose des questions aux apprenants pour connaître la compréhension des apprenants; 3) après avoir posé des questions, l'enseignant demande aux apprenants de raconter leur expériences individueles sur le thème dans la vie quotidienne; 4) les apprenants écrivent le texte comme le texte modél; 5) les apprenants révisent le texte et utiliser le texte modéle pour les aider; 6) les apprenants font le montage pour connaître l'utilisation de l'ortographe comme le texte modéle; 7) l'enseignant donne la note d'après l'évaluation de la production'écrite niveau A2 CECR.